Adult E-Learning Issues in Middle East Educational Organizations Due to Covid-19 Pandemic: Challenges and Recommendations - Omniya Mohamed; Junghwan Kim (Adult Education Research Conference, 2023)
This article reviews studies on the critical issues and challenges that adult e-learning faces in the educational sector due to the COVID-19 pandemic. The lockdown of educational organizations has forced a shift to distance learning, requiring a radical change in instructional methods. The article examines the post-pandemic learning issues that educational organizations may encounter due to the enforced e-learning process and provides recommendations for Educational Human Resources Development practitioners to overcome these challenges. A systematic literature review was conducted and analyzed to identify factors that affect adult learning during the pandemic, and the article suggests interventions that EHRD practitioners can make to address these issues. The article concludes with a discussion of the strengths and limitations of the literature and suggests areas for future research
Keywords: Keywords Online learning; informal learning; engagement issues; COVID -19 pandemic; and technology.